Characteristics of bradyarrhythmia in patients with COVID‐19: Systematic scoping review. Issue 4 (3rd March 2022) - Nagamine, Todd; Randhawa, Sandeep; Nishimura, Yoshito; Huang, Ricky; Leesutipornchai, Thiratest; Benavente, Kevin; Yoshimura, Stephanie; Zhang, James; Kanitsorphan, Chanavuth
Abstract: COVID‐19 has recently been associated with the development of bradyarrhythmias, although its mechanism is still unclear. We aim to summarize the existing evidence regarding bradyarrhythmia in COVID‐19 and provide future directions for research. Following the PRISMA Extension for Scoping Reviews, we searched MEDLINE and EMBASE for all peer‐reviewed articles using keywords including"Bradycardia, " "atrioventricular block, " and "COVID‐19″ from their inception to October 13, 2021. Forty‐three articles, including 11 observational studies and 59 cases from case reports and series, were included in the systematic review. Although some observational studies reported increased mortality in those with bradyarrhythmia and COVID‐19, the lack of comparative groups and small sample sizes hinder the ability to draw definitive conclusions. Among 59 COVID‐19 patients with bradycardia from case reports and series, bradycardia most often occurred in those with severe or critical COVID‐19, and complete heart block occurred in the majority of cases despite preserved LVEF (55.9%). Pacemaker insertion was required in 76.3% of the patients, most of which were permanent implants (45.8%). This systematic review summarizes the current evidence and characteristics of bradyarrhythmia in patients with COVID‐19. Further studies are critical to assess the reversibility of bradyarrhythmia in COVID‐19 patients and to clarify potential therapeutic targets including the need for permanent pacing.